Upaya Meningkatkan Bersihan Jalan Napas Pada Anak Dengan ISPA - Putri Rozana, Hesti; , Siti Arifah, S.Kp.,M.Kes (2017)
Acute Respiratory Infections (ARI) becomes a risk factor that can lead to increased child mortality. The cause of acute respiratory tract infections due to bacteria and viruses that cause irritation of the respiratory tract characterized by the appearance of symptoms of fever, cough, nasal congestion and the presence of additional noise. Problems often arise in ARI patients is ineffective airway clearance. Pravelensi ARI in Central Java province amounted to 3.6%. This study aims to provide nursing care to patients in improving airway clearance in patients with ARI for the assessment, formulate diagnoses, nursing interventions, implement, and evaluate action taken. The author uses descriptive method on 09 -11 February 2017 through a case study approach. In obtaining the data, the authors used several ways including through medical records, interviews, observation, physical examination, and documentation of journals and books. After nursing actions during 3x hour visit with semi-Fowler's intervention techniques, manual steam inhalation and chest physiotherapy showed the ineffectiveness of airway clearance resolved. The conclusion that the technique of semi-Fowler, steam inhalation and manual chest physiotherapy proved to be effective to improve airway clearance in children ISPA. This technique can be done anytime and good because it does not have side effects. Keyword : airway clearance, manual steam inhalation, chest physiotherapy